Inhaled Nitric Oxide Therapy for Pulmonary Disorders of the Term and Preterm Infant - Sokol, Gregory M. (Semin Perinatol, 2016)
The 21(st) century began with the FDA approval of inhaled nitric oxide therapy for the treatment of neonatal hypoxic respiratory failure associated with pulmonary hypertension in recognition of the two randomized clinical trials demostrating a significant reduction in the need for extracorporeal support in the term and near-term infant. Inhaled nitric oxide is one of only a few therapeutic agents approved for use through clinical investigations primarily in the neonate. This article provides an overview of the pertinent biology and chemistry of nitric oxide, discusses potential toxicities, and reviews the results of pertinent clinical investigations and large randomized clinical trials including neurodevelopmental follow-up in term and preterm neonates. The clinical investigations conducted by the Eunice Kennedy Shriver NICHD Neonatal Research Network will be discussed and placed in context with other pertinent clinical investigations exploring the efficacy of inhaled nitric oxide therapy in neonatal hypoxic respiratory failure.